A QUALITATIVE ANALYSIS OF THE INFLUENCE OF MANAGEMENT INFORMATION SYSTEMS ON ORGANIZATIONAL DECISION-MAKING PROCESSES - Mubashshir Bin Mahbub; Mushfiq Nabil; Taskin Ahmed (Acta Informatica Malaysia)
This qualitative research examines the profound influence of Management Information Systems (MIS) on organizational decision-making processes, focusing on how these systems serve as critical tools for enhancing strategic choices in a rapidly evolving business landscape. Through a series of in-depth semi-structured interviews with key decision-makers across diverse sectors—such as technology, healthcare, retail, construction, and consulting—this study captures the nuanced perceptions and experiences of professionals who rely on MIS to navigate complex decision-making environments. The investigation reveals six central themes that illustrate the multifaceted role of MIS: enhancing decision quality, accelerating decision-making processes, improving collaboration and communication, challenges in MIS implementation, the influence of organizational culture, and future perspectives on MIS. The analysis indicates that MIS significantly elevates decision quality by delivering real-time, accurate data and advanced analytical tools, which empower decision-makers to make informed and strategic choices. Participants articulated how access to relevant and timely information has enhanced their forecasting accuracy and overall strategic agility, enabling organizations to swiftly adapt to changing market conditions and capitalize on emerging opportunities. Moreover, the study highlights how the automation of routine data aggregation and reporting tasks facilitated by MIS contributes to the acceleration of decision-making processes. Participants emphasized that the ability to generate comprehensive reports in a fraction of the time previously required has enabled their organizations to respond more effectively to business challenges and seize competitive advantages. Despite these benefits, the research also uncovers several challenges organizations encounter in implementing and utilizing MIS effectively. A common concern expressed by participants relates to the complexity of MIS platforms and the associated learning curve that can impede initial adoption and integration. Additionally, the integrity and reliability of data generated by these systems emerged as significant challenges, with participants stressing that inaccurate or incomplete data can lead to flawed decision-making. These findings underscore the necessity for robust data governance and management practices within organizations to mitigate these risks. The analysis further underscores the critical influence of organizational culture on the success of MIS adoption. Organizations that actively promote a culture of data-driven decision-making tend to derive greater value from their MIS investments. In contrast, organizations with more traditional decision- making approaches often face resistance to embracing data analytics and may struggle to fully integrate MIS into their decision-making processes. This cultural alignment is essential for maximizing the benefits of MIS and fostering an environment conducive to innovative decision-making. Looking toward the future, participants expressed optimism about the potential of advanced technologies, such as artificial intelligence and machine learning, to enhance the capabilities of MIS and further refine decision-making processes. This forward-looking perspective highlights the growing awareness of the importance of continuous innovation and investment in technology to maintain a competitive edge in an increasingly data-driven marketplace.